2021
DOI: 10.1080/19490976.2020.1839318
|View full text |Cite
|
Sign up to set email alerts
|

Propionate catabolism by CD-associated adherent-invasive E. coli counteracts its anti-inflammatory effect

Abstract: Crohn’s disease (CD) is a chronic and disabling inflammatory disorder of the gut that is profoundly influenced by intestinal microbiota composition, host genetics and environmental factors. Several groups worldwide have described an imbalance of the gut microbiome composition, called dysbiosis, in CD patients, with an increase in Proteobacteria and Bacteroidetes and a decrease in Firmicutes . A high prevalence of adherent-invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…As shown in Figure 4D , propionate and butyrate increased flagellar gene expression and decreased capsular gene expression just as had been observed in Caco-2 coculture. The protective effect of propionate and butyrate on HIE-derived monolayers replicates what has been reported in vivo ( 22 26 ). This suggests that HIE-derived monolayers are better models of an intact intestinal epithelium than the Caco-2 monolayer.…”
Section: Resultssupporting
confidence: 86%
“…As shown in Figure 4D , propionate and butyrate increased flagellar gene expression and decreased capsular gene expression just as had been observed in Caco-2 coculture. The protective effect of propionate and butyrate on HIE-derived monolayers replicates what has been reported in vivo ( 22 26 ). This suggests that HIE-derived monolayers are better models of an intact intestinal epithelium than the Caco-2 monolayer.…”
Section: Resultssupporting
confidence: 86%
“…AIEC strains are more easily found in the CD ileum than in the CD colon. Specifically, Martinez-medina et al reported a higher incidence of AIEC in the ileum than in the colon in CD[ 77 ]. The genetic susceptibility and immune response of the intestinal flora reportedly varied with the site of disease, which means that the composition and distribution of mucosal flora may vary on the basis of the disease phenotype.…”
Section: Aiec In CDmentioning
confidence: 99%
“…A previous study has linked butyrate to commensal microbe-mediated induction of functional Treg cells [56]. A significant loss in the bacteria that produce SCFAs, such as propionate, is also a consequence of dysbiosis in CD patients [57]. The process involved in the production of SCFAs are associated with complex enzymatic pathways, accompanied by the activity of the glycolysis pathway and carbohydrate metabolism [58].…”
Section: Discussionmentioning
confidence: 99%